협계혈(GB43) 자침시 침시술 방법에 따른 SQUID MEG 신호의 변화 관찰 - 전용석(Yong srok Jeon); 장경선(Kyeong Seon Jang); 김진근(Jin geun Kim); 최찬헌(Chan Hun Choi) (동의생리병리학회지, 2005)
Using the 2-channel DROS SQUID (Korea Research Institute of Standards of Science, 1999), the present study was carried out to record changes elicited in the auditory cortex by acupuncture stimulus (right GB43, Xiaxi). Needle-retention and manual needle-twitching stimulation of GB43 and SP1 were done for acquiring the brain activities changed by acupuncture. Acupoint GB43 is known to be effective for the treatment of ear-related disease, such as deafness and tinnitus, and to be suspected to be related to the auditory cortex. Auditory evoked magnetic fields were recorded from the left hemisphere of five or four subjects, in response to contralateral ear stimulation by irregularly spaced 170msec long 1kHz tone busts (Korea Research Institute of Standards of Science). The result as follows The latency and amplitude of SQUID MEG responses at the human auditory cortex changed by needle-retention condition on GB43 were 7.2msec and 1.617, respectively, which were slower and larger than those of no-acupuncture condition. The amplitude of SQUID MEG responses at the human auditory cortex changed by needle-twitching condition on GB43 was 13.517, which was larger than that of no-acupuncture condition. The change in SP1 following GB43 needle-twitching condition were not observed in latency. The amplitude changed by needle-twitching condition on SP1 was 12.2fT, which was not significant. These results suggested that auditory cortex can be affected by acupuncture stimulus, though not specific or significant because of small number of subjects.